OAS – Anatomy of a Terror Organisation - Kovács, Tamás (Magyar Rendészet, 2025)
The Organisation Armée Secrète (Secret Army Organisation, OAS) was a prominent French terrorist organisation that operated during the 1960s. The organisation’s establishment is inextricably linked to the Algerian War. A significant proportion of the French military elite and the French population resident in Algeria opposed the country becoming an independent state. Following the protracted nature of the conflict, the newly elected French President, Charles de Gaulle, resolved to conclude the War in Algeria. This, of course, meant that Algeria would no longer be a French colony. Nevertheless, the decision was not universally accepted. In particular, the French settlers in Algeria and members of the army and the Foreign Legion felt that some action was necessary to maintain Algeria’s status as a French territory. These forces ultimately gave rise to the Organisation de l’Armée Secrète (OAS).